Congenital neurofibroma with hypertrichosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
This is a 6-month-old little girl with a neoformation of the mesogastric region, noted by her mother at the age of two months. The physical examination showed a localized hypertrichosis without color changes of the skin (Fig. 1) and on palpation a rectangular, 2 x 1.6 cm, sharply delimited plaque with smooth surface and hard consistency (Fig. 2). Despite the absence of contractility we clinically diagnosed nevus leiomyoma. After one month the baby came back because at the periphery of the plaque two smaller tumors with similar characteristics had appeared. A biopsy was performed and the histological examination showed in the deep dermis at the boundary with the subcutaneous fat a barely delimited neoformation (Fig. 3) of spindle cells with S-shaped nuclei sometimes associated with thin nerve bundles (Fig. 4), leading to the final diagnosis of congenital neurofibroma with hypertrichosis.